Relationship of being threatened or injured with a weapon in school with suicidal ideation and attempt among school students: a school-based study in Zhejiang Province, China - Hao Wang; Huaidong Du; Fiona Bragg; Jieming Zhong; Min Yu (BMC, 2018)
Abstract Background Suicide is the second leading cause of death among 15-29 year old youths globally, and the third most common external cause of death in China. School bullying can cause serious consequences among adolescents, including psychosocial problems, low self-esteem and post-traumatic stress disorder. Most studies examining the associations between being bullied in school and suicide are from Western, developed countries. Moreover, few studies focus on being threatened or injured with a weapon, which may cause serious body injury. Our study aimed to explore the relationship of being threatened or injured with a weapon in school with suicidal ideation and attempt among middle and high school students in Zhejiang Province, China. Methods A cross-sectional study of 23,543 students in grades 7-12 from 442 schools was carried out through an anonymous self-administered questionnaire between April and May 2017. Multivariable logistic regression models were used to examine the relationship of being threatened or injured with a weapon in school with suicidal ideation and attempt. Results 51.3% of participants were boys, and mean (SD) age was 15.6 (1.7) years. The overall prevalence of suicidal ideation and attempt were 16.1% (95%CI: 15.3-16.9) and 3.6% (95%CI: 3.3-4.0), respectively. Prevalence was higher among girls than boys (ideation: 19.1% vs. 13.3%. attempt: 4.4% vs. 2.9%). 13.2% of students reported being threatened or injured with a weapon in school in the past 12 months (95%CI: 11.9-14.5), higher among boys than girls (15.7% vs. 10.5%), and among rural students than urban students (13.9% vs. 11.6%). After adjustment for socio-demographic status, lifestyle factors, academic performance, self-reported health and mental health, the odds ratios for suicidal ideation and attempt among students who reported being threatened or injured with a weapon were 1.46 (1.31-1.61) and 1.68 (1.31-2.13) respectively, as compared with those who did not report being threatened or injured. Conclusions Preventive measures for physical bullying in school need to be reinforced in China. Being threatened or injured with a weapon is associated with both suicidal ideation and attempt among middle and high school students. Suicide prevention should be an important component of psychological interventions for threatened or injured students.